2020
DOI: 10.1111/jhn.12834
|View full text |Cite
|
Sign up to set email alerts
|

British Dietetic Association’s Obesity Specialist Group dietetic obesity management interventions in children and young people: review & clinical application

Abstract: Background Dietitians play a vital role in the management of childhood obesity. To support that role the Obesity Specialist Group of the British Dietetic Association commissioned a review and clinical application paper. This current paper is a summary of that review document, which is available on the BDA’s website. Methods The initial sources of evidence were guidelines, published reviews and government guidance. Best practice advice was sought from networks including the BDA’s Obesity and Paediatric Speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is important to remember that just because we can measure something doesn't mean we should. In keeping with our aim to reflect the breadth and multidisciplinary nature of nutrition and dietetics research, JHND favours papers that advance the field, 15,16 establish novel methodologies and research tools, 17,18 have clinical impact, 19,20 and establish professional guidelines 21 …”
Section: Keeping Originality In Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to remember that just because we can measure something doesn't mean we should. In keeping with our aim to reflect the breadth and multidisciplinary nature of nutrition and dietetics research, JHND favours papers that advance the field, 15,16 establish novel methodologies and research tools, 17,18 have clinical impact, 19,20 and establish professional guidelines 21 …”
Section: Keeping Originality In Focusmentioning
confidence: 99%
“…In keeping with our aim to reflect the breadth and multidisciplinary nature of nutrition and dietetics research, JHND favours papers that advance the field, 15,16 establish novel methodologies and research tools, 17,18 have clinical impact, 19,20 and establish professional guidelines. 21 The best pathway to having research published is to do research that is worthwhile and inspires others to read and build on the findings. Most of the research surrounding Covid-19 and nutrition was opportunistic, unplanned and will have no future application.…”
Section: Keeping Originality In Focusmentioning
confidence: 99%
“…It has been suggested that, to provide advice targeted towards specific food components (for example the reduction of the consumption of carbonated drinks and sugary foods or foods with a high caloric density), is more effective in weight control than providing advice on healthy eating. Supporting these long-term dietary changes has the potential to improve energy balance and decrease the BMI z-score in children and adolescents aged 2-18 years [21][22][23].…”
Section: Non-restrictive Approachmentioning
confidence: 99%
“…Rapid brain development occurs between 0 and 5 years of age [ 101 , 102 ]. Preschoolers are advised to consume frequent and balanced meals in adequate proportions [ 103 ]. Their daily diet should include at least five varieties of vegetables and fruits beside lean proteins and carbohydrates [ 104 ].…”
Section: Consultation Perspectivementioning
confidence: 99%